Rare copy number variants in over 100,000 European ancestry subjects reveal multiple disease associations - Yun Rose Li (Nature Portfolio, 2020)
Associations of copy number variations (CNVs) with complex traits are challenging to study because of their low frequency. Here, the authors analyse SNP array and array comparative genomic hybridization data of 100,028 individuals and report their associations with immune-related, cardiometabolic and neuropsychiatric diseases as well as cancer.